DELIK MUTILASI DALAM PERSPEKTIF HUKUM, VIKTIMOLOGI DAN KRIMINOLOGI - Fathol Bari (HUKMY : Jurnal Hukum, 2022)
In Indonesia, there are many legal norms that already regulate murder, including mutilation. The crime of mutilation has been regulated in various laws and regulations in Indonesia. Criminology perspective mentions or outlines in the discussion of the problems of the factors causing the occurrence of criminal acts of mutilation and modus operandi of crimes or criminal acts of mutilation, especially those that occur in Indonesia. The victimology perspective emphasizes the aspect of the victim, that is, when a person becomes a victim of a criminal act of mutilation, why can someone become a victim of mutilation. Because these crimes are rare or only occur in certain perpetrators, so the study is not easy, especially related to the position of the victim.